2021
DOI: 10.1007/s10980-021-01376-7
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: the landscape matrix determines the population genetic structure of temperate forest herbs across Europe

Abstract: Context Plant populations in agricultural landscapes are mostly fragmented and their functional connectivity often depends on seed and pollen dispersal by animals. However, little is known about how the interactions of seed and pollen dispersers with the agricultural matrix translate into gene flow among plant populations. Objectives We aimed to identify effects of the landscape structure on the genetic diversity within, and the genetic differentiation amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 93 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…For example, the amount of fake pollen transported by bumblebees among populations of Primula vulgaris was higher above grassland than above cropland (Van Geert et al, 2014). Woodland and grassland, at the expense of cropland in the landscape surrounding P. multiflorum populations increased allelic richness and reduced heterozygote excess (Naaf et al, 2021(Naaf et al, , 2022. It is also likely that our movement indicators reflect a certain landscape composition.…”
Section: Landscape Composition Might Influence the Genetic Linkage Of...mentioning
confidence: 88%
“…For example, the amount of fake pollen transported by bumblebees among populations of Primula vulgaris was higher above grassland than above cropland (Van Geert et al, 2014). Woodland and grassland, at the expense of cropland in the landscape surrounding P. multiflorum populations increased allelic richness and reduced heterozygote excess (Naaf et al, 2021(Naaf et al, , 2022. It is also likely that our movement indicators reflect a certain landscape composition.…”
Section: Landscape Composition Might Influence the Genetic Linkage Of...mentioning
confidence: 88%
“…Different from A. nemorosa , which is associated with short‐distance, forest‐specialized pollinators (Feigs et al., 2022 ), P. multiflorum is pollinated by bumblebees (Kosiński, 2012 ) that are able to fly over a heterogeneous landscape (Persson & Smith, 2011 ). During the forest fragmentation period, large forest habitats of P. multiflorum were turned into a large number of small patches (Figure 2 ), intersected with many other land‐use types, including bumblebee friendly land‐use types, such as grassland and hedgerows (Byrne & delBarco‐Trillo, 2019 ; Naaf et al., 2022 ). This type of heterogeneous habitat may benefit bumblebee species not specific to forest by providing nesting and foraging sites (Gómez‐Martínez et al., 2020 ), which may in turn facilitate a higher genetic connectivity of younger P. multiflorum populations than of older ones.…”
Section: Discussionmentioning
confidence: 99%
“…Gene flow among plant populations is largely influenced by the environment outside of their actual habitats, since the surrounding environment contributes to the habitat of pollinators or seed vectors (Breitbach et al., 2012 ; Jauker et al., 2009 ). Thus, we might find more species‐specific patterns if we take the landscape structure into account (Naaf et al., 2022 ). This was, however, beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we created digital land‐use maps with ESRI ArcGIS Map version 10.8.2 (Figure S2 ) for the three landscape windows based on recent orthophotos according to Naaf et al. ( 2022 ). For arable fields, we also differentiated the dominance of three different crop types, that is, oil seed rape, maize and other cereals, over the preceding decade (Figures S2.3–S2.5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies have suggested that the landscape composition in between the forest patches may also shape the herbs' population genetic structure (Decocq et al., 2021 ; Guiller et al., 2023 ; Schmidt et al., 2009 ). In fact, the landscape composition might even exert a greater influence on the population genetic structure of forest herbs than habitat loss and fragmentation per se (Naaf et al., 2022 ). Review articles for various types of mosaic‐like landscapes highlight that landscape composition is a major determinant of functional connectivity of plant populations (Driscoll et al., 2013 ; Murphy & Lovett‐Doust, 2004 ).…”
Section: Introductionmentioning
confidence: 99%